Surgical Management of Dystocia Due to Uterine Torsion in a Persian Cat - Yadav, Lakshmi; Singh Gurjar, Kuldeep; Purohit, Shivani (The Indian Journal of Animal Reproduction, 2025)
A female Persian cat having four years of age was presented with history of fifty eight days of gestation, anorexia, vaginal  discharge and abdominal distension at Veterinary Clinical Complex, PGIVER Jaipur. The female cat had delivered three  dead fetus, showing crying behavior. Radiography revealed presence of three underdeveloped fetus and ultrasonography  was performed which showed no cardiac activity. An emergency caesarean section was performed which discovered  uterine torsion of 360° in right horn. Thereafter, an ovariohysterectomy was performed as the uterus was necrosed under  general anaesthesia. After receiving fluid therapy and antibiotics, the patient recovered and regained appetite a few days  after the surgery.
Keywords: Uterine torsion; Radiography; Ultrasonography; Caesarean section; Abdominal distension.